2003
DOI: 10.1080/0955300031000073400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiation on Ewing tumour subpopulations characterized on a single-cell level: intracellular cytokine, immunophenotypic, DNA and apoptotic profile

Abstract: The changed profile of tumour cells under radiation might be associated with biological changes of tumour subpopulations in view of radioresistance and metastatic potential and might be useful to identify intercellular regulation mechanisms and to define parameters being predictive for a response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Notably, the expression of CD54 (intercellular cell adhesion molecule-1 [ICAM1]), CD117 (c-kit), and CD271 (low-affinity nerve growth factor receptor [LNGFR]) increased in EWS/ETS-expressing UET-13 cells. These markers are positive in EFT cell lines (17,28,33), and in addition, CD117 is detected in about 40% of patient samples (17) and is negative in human primary MPCs (4,43). Thus, it is reasonable to consider that a phenotypic marker of EFT was induced in UET-13 cells by EWS/ETS expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the expression of CD54 (intercellular cell adhesion molecule-1 [ICAM1]), CD117 (c-kit), and CD271 (low-affinity nerve growth factor receptor [LNGFR]) increased in EWS/ETS-expressing UET-13 cells. These markers are positive in EFT cell lines (17,28,33), and in addition, CD117 is detected in about 40% of patient samples (17) and is negative in human primary MPCs (4,43). Thus, it is reasonable to consider that a phenotypic marker of EFT was induced in UET-13 cells by EWS/ETS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Human MPCs reveal a characteristic expression of several surface antigens and can be identified on the basis of the reactivity with a set of monoclonal antibodies against CD antigens (25,42). On the other hand, some CD antigens are characteristically expressed on EFT cells (17,28,33). Using the combinations of these antibodies listed in Table 2, which are useful for the immunodetection of either MPCs or EFT cells, we further examined whether EWS/ETS expression affects the immunophenotype of UET-13 cells and compared its effect with that on the immunophenotype of EFT cell lines (Table 2 and Fig.…”
Section: Vol 28 2008 Effects Of Ews/ets Expression In Human Mpcs 2129mentioning
confidence: 99%
“…14 We now focused on the markers HLA-ABC, CD11a and CD62L because our results indicated that these markers might be informative to detect heterogeneity in view of radiation induced apoptosis. These markers are described to be involved in apoptosis related pathways and in the clearance process of apoptotic cells.…”
Section: Introductionmentioning
confidence: 95%
“…A simultaneous characterization of light scatter properties, surface molecules, DNA content, and apoptosis-associated markers can be performed at a single cell level. [11][12][13][14] As an early marker of apoptosis the binding of Annexin V to phosphatidylserine on the cell membrane can be used. 15 In addition, the staining of the DNA with dyes like 7-AAD without any permeabilisation of the cell membrane allows the characterization of the integrity of the cell membrane and is therefore a useful marker for characterization of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric flow cytometry is an effective, reliable and fast technique to characterize tumour cells and identify interindividual heterogeneity and subpopulations within one individual tumour. Using this method, the simultaneous characterization of cell surface antigens, intracellular cytokines, DNA content and apoptosis-associated markers can be used at a single cell level (Hollander and Loken 1988, Brons et al 1990, Stokke et al 1991, Orfao et al 1995, Prussin and Metcalfe 1995, Corver et al 1996, Jason and Larned 1997, Könemann et al 2000, 2003, Bacso and Eliason 2001, Rasola and Geuna 2001.…”
Section: Introductionmentioning
confidence: 99%